Characterization of age-related immune features after autologous NK cell infusion: Protocol for an open-label and randomized controlled trial - Tang, Xiaofeng; Deng, Biaolong; Zang, Aiping; He, Xiaowen; Zhou, Ye; Wang, Daimeng; Li, Dan; Dai, Xueyu; Chen, Jieqiong; Zhang, Xuhua; Liu, Ye; Xu, Yonghua; et al. (Frontiers in Immunology, 2022)
Background Aging is usually accompanied by functional declines of the immune system, especially in T-cell responses. However, little is known about ways to alleviate this. Methods Here, 37 middle-aged healthy participants were recruited, among which 32 were intravenously administrated with expanded NK cells and 5 with normal saline. Then, we monitored changes of peripheral senescent and exhausted T cells within 4 weeks after infusion by flow cytometry, as well as serum levels of senescence-associated secretory phenotype (SASP)-related factors. In vitro co-culture assays were performed to study NK-mediated cytotoxic activity against senescent or exhausted T cells. Functional and phenotypic alteration of NK cells before and after expansion was finally characterized. Results After NK cell infusion, senescent CD28-, CD57+, CD28-CD57+, and CD28-KLRG1+ CD4+ and CD8+ T-cell populations decreased significantly, so did PD-1+ and TIM-3+ T cells. These changes were continuously observed for 4 weeks. Nevertheless, no significant changes were observed in the normal saline group. Moreover, SASP-related factors including IL-6, IL-8, IL-1α, IL-17, MIP-1α, MIP-1β, and MMP1 were significantly decreased after NK cell infusion. Further co-culture assays showed that expanded NK cells specifically and dramatically eliminated senescent CD4+ T cells other than CD28+CD4+ T cells. They also showed improved cytotoxic activity, with different expression patterns of activating and inhibitory receptors including NKG2C, NKG2A, KLRG1, LAG3, CD57, and TIM3. Conclusion Our findings imply that T-cell senescence and exhaustion is a reversible process in healthy individuals, and autologous NK cell administration can be introduced to alleviate the aging. Clinical Trial Registration ClinicalTrials.gov, ChiCTR-OOh-17011878.